Comparative Study of Recombinant Human Erythropoietin (rhEPO) Products on CKD (Chronic Kidney Disease) Patients - Dwitanto, Kuspuji; Angginy, Nova; Sutandar, Widodo (Drug Research, 2023)
Purpose This study was conducted to evaluate whether the efficacy and safety profile of recombinant human erythropoietin (rhEPO) manufactured by Daewoong Pharmaceutical Co., Ltd was similar to biological products approved by the drug safety regulatory authority.Patients and methods It was an open-label, randomized, comparative, parallel, multi-center study in hemodialysis patients with anemia. The reference product at an individualized dose 3 times a week was given in 4–8 weeks of titration period and hemoglobin (Hb) level was controlled to reach the range of 10–12 g/dL. Then, the subjects were randomly administered with reference or test product with the same dose regimen. The primary endpoints were to demonstrate the Hb level change between baseline and evaluation period in both treatment groups, while the secondary endpoints were the mean change in weekly dosage per kg body weight and the instability rate of Hb level during maintenance and evaluation period. The safety was evaluated based on the adverse events incidence.Results There was no statistical difference in the change of Hb between test and reference (0.14 g/dL and 0.75 g/dL respectively, with p>0.05), also for the mean changes of weekly dosage between groups (1091.40 IU and 570.15 IU respectively, with p>0.05). The instability rate of Hb in both test and reference was not statistically significantly different as well (26 and 15% respectively, with p>0.05).Conclusion This study proves that the efficacy indicated by the change instability of Hb and safety indicated by adverse event incidence of Epodion and the reference product on chronic kidney disease were similar.
Keywords: comparative; erythropoietin; CKD; Anemia